Experimental characterization of inhibited carbon dioxide hydrates above the upper quadruple point Caracterização experimental de hidratos de dióxio de carbono inibidos acima do ponto quádruplo superior - Cordeiro Junior, José Carlos (2019)
Under specific conditions, water molecules can combine with gas molecules forming a solid crystalline structure called hydrates. The formation of this ice-like phase can block pipelines and is a major flow assurance concern in oil and gas industries. Carbon dioxide is a natural contaminant present in petroleum. As oilfields are being explored in regions with more severe conditions, it can condensate and thus an upper quadruple point appears in the hydrate phase equilibrium. Above this point, hydrate forms from liquid carbon dioxide and water. Thermodynamic inhibitors, such as MEG, are commonly used in petroleum industry and act by changing the conditions at which hydrates can form, essentially preventing their appearance. In offshore oil and gas production, water that can potentially form hydrates is naturally inhibited with salts. This way, the use of thermodynamic inhibitors can be optimized with the presence of salts. With this in mind, the influence of NaCl and MEG in the phase equilibrium of carbon dioxide hydrates was evaluated. An equilibrium cell connected to a syringe pump was used to determine experimental phase equilibrium points of inhibited carbon dioxide hydrates. In order to achieve high pressures to ensure the condensation of the gas phase, an isobaric procedure was used. By changing the temperature of the cell, hydrates form, consuming CO2, which is replaced by the syringe pump in order to keep a constant pressure. New equilibrium experimental data for pressures varying from 8.5 to 25 MPa were determined. The consistency of the data collected was evaluated with good results, confirming its reliability. Lastly, the experimental data collected were compared with prediction software products and models in order to evaluate their accuracy. Commercial software Multiflash and PVTSim offered good results for systems inhibited with MEG and NaCl, while the open source CSMGem software was able to give decent results in pure water system and with mixture of inhibitors, except in high concentrations, where it greatly super-estimated the inhibition effect. Sirino et al. (2018) and the Hu-Lee-Sum correlation were conservative on its results, generally sub-estimating the inhibition effect of inhibitors.